Potential of Dried Blood Self-Sampling for Cyclosporine C2 Monitoring in Transplant Outpatients - Alexander Benedikt Leichtle; Uta Ceglarek; Helmut Witzigmann; Gábor Gäbel; Joachim Thiery; Georg Martin Fiedler (Journal of Transplantation)
Background. Close therapeutic drug monitoring of Cyclosporine (CsA) in transplant outpatients is a favourable procedure to maintain the long-term blood drug levels within their respective narrow therapeutic ranges. Compared to basal levels (C0), CsA peak levels (C2) are more predictive for transplant rejection. However, the application of C2 levels is hampered by the precise time of blood sampling and the need of qualified personnel. Therefore, we evaluated a new C2 self-obtained blood sampling in transplant outpatients using dried capillary and venous blood samples and compared the CsA levels, stability, and clinical practicability of the different procedures. Methods. 55 solid organ transplant recipients were instructed to use single-handed sampling of each 50 μL capillary blood and dried blood spots by finger prick using standard finger prick devices. We used standardized EDTA-coated capillary blood collection systems and standardized filter paper WS 903. CsA was determined by LC-MS/MS. The patients and technicians also answered a questionnaire on the procedure and sample quality. Results. The C0 and C2 levels from capillary blood collection systems (C0 [ng/mL]: 114.5±44.5; C2: 578.2±222.2) and capillary dried blood (C0 [ng/mL]: 175.4±137.7; C2: 743.1±368.1) significantly (P<.01) correlated with the drug levels of the venous blood samples (C0 [ng/mL]: 97.8±37.4; C2: 511.2±201.5). The correlation at C0 was ρcap.-ven. = 0.749, and ρdried blood-ven = 0.432; at C2:   ρcap.-ven. = 0.861 and ρdried blood-ven = 0.711. The patients preferred the dried blood sampling because of the more simple and less painful procedure. Additionally, the sample quality of self-obtained dried blood spots for LC-MS/MS analytics was superior to the respective capillary blood samples. Conclusions. C2 self-obtained dried blood sampling can easily be performed by transplant outpatients and is therefore suitable and cost-effective for close therapeutic drug monitoring.